IR Detection of Impact Places of Projectiles in the Training System “ŚNIEŻNIK” - Waldemar ŚWIDERSKI; Tomasz GŁOGOWSKI; Paweł HŁOSTA; Sławomir STĘPNIAK (Problemy Mechatroniki)
Multimedia laser-shooting training systems are more and more frequently used for trainings uniformed services and protective formations. One of the subsequent stages of the development of the “Śnieżnik” system is the possibility of training with weapon and combat ammunition, basing on dynamic scenarios and moving targets displayed on a screen. The paper presents application of IR for detection of the impact place of the projectile of combat or blank ammunition.